2012
DOI: 10.4321/s1886-36552012000400005
|View full text |Cite
|
Sign up to set email alerts
|

Women and men report different behaviours in, and reasons for medication non-adherence: a nationwide Swedish survey

Abstract: ObjectiveThe aim of the present study was to analyse gender differences in self-reported non-adherence (NA) to prescribed medication in the Swedish general population. We aimed to study unintentional and intentional NA as well as the reasons given for NA.MethodsA questionnaire was mailed to a cross-sectional, random, national sample of people aged 18-84 years in Sweden (n=7985). The response rate was 61.1% (n=4875). The questionnaire covered use of prescription drugs, NA behaviour and reasons for NA.ResultsUse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 60 publications
3
35
2
Order By: Relevance
“…This is consistent with the previous finding in the cancer patients and in general population [10,17]. It is less clear if this is in part due to that women are more price sensitive to out-of-pocket payment for medication, have different perception of the effectiveness of medication, or differential level of health literacy.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with the previous finding in the cancer patients and in general population [10,17]. It is less clear if this is in part due to that women are more price sensitive to out-of-pocket payment for medication, have different perception of the effectiveness of medication, or differential level of health literacy.…”
Section: Discussionsupporting
confidence: 90%
“…Men and women have different health behaviors21 and also different attitudes toward drugs22,23 and have in previous studies been found to have different NA behaviors and different reasons for NA 1,2,4. As regards men and women with anxiety and/or depression, knowledge about the effects of sex on adherence is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 50%–60% of all patients show poor medication adherence and NA is considered the most common reason for treatment failure 1,2. NA can be either unintentional (eg, forgetting to take the medication) or intentional (a more active decision that can involve changing the dosage or not taking the drug at all) 3,4. Health care professionals worldwide are asking why patients do not take the drugs as prescribed, despite the perception that the treatment is offered in consensus with the patient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gender and age of owners were not related to medication adherence in this sample. The published literature shows that women are, in general, more adherent than men [18,19], and that having a caregiver does not necessarily improve medication adherence [20]. Although the sample had a mean age below 40 years, the lack of association between adherence and owners' age might suggest an opportunity to use m-health apps independently from the age of the caregiver.…”
Section: Discussionmentioning
confidence: 97%